The Legal Problems of Ownership and Management of The Natural Resources Between The Governance Levels of Federal Iraq “ The Case of Ownership and Management of Oil and Gas” (Raparin Journal of Humanities (RJH), 2020)
Federalism is a system of power-sharing and decision-making between levels of government.Federalism also protects the unity of the state and its political entity. On the other hand, Give the States their share of power and wealth (Resources) and then prevent the establishment of authoritarian governments.   And Iraq's 2005 constitution has produced a sharp difference between the federal government and the KRG about the management and collection of oil and gas revenues. Therefore we see that we should study the powers and competencies of both authorities because the Constitution of Iraq adopted a federal system for the regions.  And this research tries to reveal the Iraqi federal experience, which was adopted by the Constitution and how to use this experience to manage and Invest natural resources and resolve the expected conflicts upon these resources.